P-379 Ongoing pregnancy rate (OPR) of day (D) 7 euploid blastocysts is inferior to D5/D6 euploid blastocysts in frozen embryo transfer (FET) cycles. (30th June 2022) - Abdala, A; Elkhatib, I; Bayram, A; El-Damen, A; Nogueira, D; Melado, L; Lawrenz, B; Fatemi, H
Abstract: Study question: Do delayed-grown D7 euploid blastocysts have similar OPRs as D5 or D6 euploid blastocysts in FET cycles? Summary answer: Although OPR is significantly higher with D5/D6 euploid blastocysts than D7, patients aged >38 years might benefit when slow-developing blastocysts are routinely cultured till D7. What is known already: Current IVF practice suggests that embryos of optimal development reach blastocyst stage 116±2 hours after insemination. Recently, high reproductive potential has been reported with D6 as well as with D7 blastocysts. Although D7 blastocysts have a delayed embryo development, euploidy rates range between 25% and 49% if biopsy is performed. Usable D7 blastocysts represent nearly 5% of embryos in IVF with acceptable pregnancy and live birth rates, however, data are still limited. Therefore, further evidence of FET outcomes with D5, D6 and D7 euploid blastocysts are needed to investigate whether prolonged in-vitro embryo culture till D7 should be performed routinely. Study design, size, duration: A single centre observational study was performed between June 2017 and November 2021, including 1396 single euploid FET cycles with blastocysts biopsied on D5 (N = 795), D6 (N = 572) or D7 (N = 29). Patients underwent endometrial preparation for a FET in a natural cycle (NC) or hormone replacement treatment (HRT). Only blastocysts graded ≥ BL3CC (Gardner scoring) before trophectoderm (TE) biopsy on D5, D6 or D7, which re-expanded within 1-hour post-warming, were considered in the analysis. Participants/materials, setting, methods: All warmed blastocysts were transferred after 120 hours of progesterone (P4) exposure. In NC, P4 was administered after ovulation until pregnancy test (PT). For HRT cycles, estradiol was prescribed until endometrial thickness reached ≥6 mm or a trilaminar pattern was seen on which P4 was supplemented until PT. OPR was recorded at 12 weeks by the presence of a gestational sac/s and fetal heartbeat. A multivariate logistic regression model with generalized estimating equation was performed. Main results and the role of chance: Women's mean age differed significantly for FET cycles performed with D5, D6 and D7 euploid blastocysts (33.2±5.6, 34.5±5.3 and 36.1±4.5 years old; P < 0.001) as well as AMH values (ng/mL) (3.6±3.6, 2.9±2.8 and 2.3±1.8; P < 0.001; respectively). OPR with D5 euploid blastocysts was significantly higher than D6 and D7 (55.6%, 44.9% and 10.3%; P < 0.001), however, miscarriage rates did not differ (9.3%, 6.6% and 6.9%; P = 0.201; respectively). Following an adjusted multivariate logistic regression model, the factors associated with a reduced OPR were: D7 FETs (OR: 0.19 [0.06-0.63]; P = 0.006), ICM grade C (OR: 0.29 [0.17-0.48]; P < 0.001) and TE grade C (OR: 0.58 [0.38-0.89]; P = 0.012). Contrary, OPR outcomes were increased in NC compared to HRT cycles (OR: 1.35 [1.06-1.71]; P = 0.013). A sub-analysis showed that advanced maternal age was a risk factor of having a D7 FET cycle (OR: 1.09 [1.01-1.17]; P = 0.025). In patients >38 years, OPR was improved if D7 FET cycles were performed however, this finding was nonsignificant (OR: 2.33 [0.19-29.4], P = 0.510). In patients <38 years, D7 FET cycles were significantly negatively associated with OPR outcomes (OR: 0.07 [0.01-0.54], P = 0.011). Regardless of patient's age, OPR outcomes with D5/D6 were higher than D7 FETs. Limitations, reasons for caution: The current results are based on an observational study including a limited sample size of D7 euploid blastocysts FET cycles. Additionally, live birth rates should be considered in a further analysis to validate the performance of D5 and D6, compared to D7 euploid blastocysts, in both, NC and HRT cycles. Wider implications of the findings: Considering age as a risk factor of having delayed grown blastocysts in-vitro, culturing embryos till D7 can be a strategy to increase OPR in patients >38 years old. With an increase in age, patients are more likely to have blastocysts biopsied on D6/D7. OPR outcomes are increased in NC FETs. Trial registration number: non-clinical trials